Measuring green jobs: a new database for Latin America and other regions - Winkler, Hernán Jorge (2024)
A growing body of literature investigates the labor market implications of scaling up “green” policies. Since most of this literature is focused on developed economies, little is known about the labor market consequences for developing countries. This paper contributes to filling this gap by providing new stylized facts on the prevalence of green occupations and sectors across countries at varying levels of economic development. Green occupations are defined using the Occupational Information Network, and green sectors are those with relatively lower greenhouse gas emissions per worker. The paper offers an initial assessment of how the implementation of green policies—aimed at expanding green sectors and strengthening the relative demand for green skills—may affect workers in developing economies. It finds that the share of green jobs is strongly correlated with the level of gross domestic product per capita across countries. When controlling for unobserved heterogeneity, a 1 percent increase in gross domestic product per capita is associated with 0.4 and 4.1 percentage point increases in the shares of new and emerging, and enhanced skills green jobs, respectively. The paper then focuses on Latin America and finds that only 9 percent of workers have a green job with respect to both occupation and sector. The findings show that within countries, workers with low levels of income and education are more likely to be employed in non-green sectors and occupations, and to lack the skills for a greener economy. This evidence suggests that complementary policies are needed to mitigate the potential role of green policies in widening income inequality between and within countries.